PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, LEVERAGE, FIRM SIZE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN HIGH PROFILEYANG TERDAFTAR DI BURSA EFEK INDONESIAPERIODE TAHUN 2008-2012 - WIBAWATI SHOLEKAH, FEBRINA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract :The research aims to exemine the influence of managerial ownership, institutional ownership, leverage, firm size, and corporate social responsibilityon firm value. The samples at this research are high profile companies listed in Indonesian Stock Exchange during period of 2008-2012. Data usedfromannualreport.Technique analysis usedmultiple linear regression. The results showingthatthere are threeindependentvariablesthataffect thedependent variable ismanagerial ownership, CSR, Leverageis influence firm value. Institutionalownershipisnot effecton firm value.institutional investorswithsmallshareholdingswillperformweak oversightof themanagerialdecisionsandactions, whichmayaffectmanagerialdecisionsrise and fall ofthe value ofthe company. Firmsizehas not influenceon firm value. Dueto theincrease intotal assetsownedbythe companymaynot necessarilyincrease thevalue ofthe companyin the eyes ofinvestors. Keywords:corporatevalues??, managerial ownership, institutional ownership, leverage, firm size and corporate social responsibility.